UL54 foscarnet mutation in an hematopoietic stem cell transplant recipient with cytomegalovirus disease. Issue 2 (13th March 2014) - Gregg, K.; Hakki, M.; Kaul, D.R.
Abstract We present a case of foscarnet (FOS) resistance arising from a UL54 mutation after a short duration of FOS exposure, which has not been previously described in a stem cell transplant recipient, to our knowledge. We discuss the use of FOS to treat other viral infections and the implications this may have for the development of resistance mutations and treatment of cytomegalovirus disease.